Peningkatan Keterampilan Passing Bawah Dalam Permainan Bola Voli Melalui Metode Sitektif - Veri (IKIP PGRI Pontianak, 2023)
The purpose of this study is to what extent the application of the Selective method can improve the skills of underhand passing in volleyball games for fifth grade students at SDN 06 Tanjung Gunung. To improve lower passing skills in volleyball games, a design was carried out using the Classroom Action Research Method (CAR), with four stages consisting of planning, implementing actions, observing and reflecting which are carried out systematically. With the research subject of class V students at SDN 06 Tanjung Gunung totaling 38 students. The data collection tool uses observation sheets and passing tests under volleyball games. From the results obtained after completing cycle I and cycle II, the learning of underhand passing skills in volleyball games through the Detective method showed quite satisfactory results. This can be seen from the average Pre-Implementation score of 23.4 to 28.2 in cycle I, or an increase of 20.5%. But in this first cycle, the percentage of students who got grades ≥ B was only 42%. Whereas in cycle II the average value of students rose to 33.9 or an increase of 44.8%. In cycle II, the percentage of students who scored ≥B reached 73.6%, this result has reached the target of 70% of the total number of students. It can be concluded that the systematic method provides an increase in lower passing skills in volleyball games at SDN 06 Tanjung Gunung.